Synthesis of Thiazolopyrimidines via Annulation of N‐(4, 6‐Diaryl‐2‐thioxo‐1, 2, 3, 6‐tetrahydropyrimidin‐4‐yl)phenyl)aryl‐sulfonamides. Issue 9 (5th March 2018) - Bahekar, Sandeep P.; Chandak, Hemant S
Abstract: A series of 5, 7‐diaryl‐5 H ‐thiazolo[3, 2‐a]pyrimidin‐3(2 H )‐ones(4 a‐4 r) bearing sulfonamide scaffold have been synthesized by cyclocondensation of bromoacetic acid and N ‐(4, 6‐diaryl‐2‐thioxo‐1, 2, 3, 6‐tetrahydropyrimidin‐4‐yl)phenyl)aryl‐sulfonamides(3 a‐3ab) . Compounds3 a‐3ab have been synthesized by cyclocondensation of sulfonamide chalcones(1) and thiourea. Acetic acid: acetate buffer system and temperature of the reaction system played an important role in conversion of3 to4 . The synthesized compounds were evaluated for their in vitro anticancer activities against the strain of human breast cancer cell line MCF‐7. Compounds3 e, 3 p, 4 h and4 k with GI50 below 80 μM were found to be moderately cytotoxic against MCF‐7. Abstract : A series of N ‐(4, 6‐diaryl‐2‐thioxo‐1, 2, 3, 6‐tetrahydropyrimidin‐4‐yl)phenyl)aryl‐sulfonamides and 5, 7‐diaryl‐5 H ‐thiazolo[3, 2‐a]pyrimidin‐3(2 H )‐ones bearing sulfonamide scaffold have been synthesized and evaluated for their in vitro anticancer activities against the strain of human breast cancer cell line MCF‐7.